2023
DOI: 10.1097/hrp.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Repetitive Transcranial Magnetic Stimulation to Treat Major Depression: The Past, Present, and Future

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is an effective and evidence-based therapy for treatment-resistant major depressive disorder. A conventional course of rTMS applies 20-30 daily sessions over 4-6 weeks. The schedule of rTMS delivery can be accelerated by applying multiple stimulation sessions per day, which reduces the duration of a treatment course with a predefined number of sessions. Accelerated rTMS reduces time demands, improves clinical efficiency, and potentially induces faster onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 166 publications
(428 reference statements)
0
5
0
Order By: Relevance
“… 6 Furthermore, daily multiple treatment sessions of accelerated rTMS can reduce the overall treatment duration, enhance clinical efficiency, and expedite the onset of antidepressant effects. 7 Notably, 4 sessions per day of accelerated rTMS were found to be more effective than intranasal esketamine. 8 …”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Furthermore, daily multiple treatment sessions of accelerated rTMS can reduce the overall treatment duration, enhance clinical efficiency, and expedite the onset of antidepressant effects. 7 Notably, 4 sessions per day of accelerated rTMS were found to be more effective than intranasal esketamine. 8 …”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…In rTMS, HF-rTMS is an U.S. Food and Drug Administration (FDA)-approved technique for the treatment of treatment-resistant depression (TRD). 5 Bilateral rTMS 6 and accelerated rTMS 7 are promising techniques for treating MDD. A meta-analysis reported that bilateral rTMS is a potentially effective treatment for MDD, offering clinically significant benefits over standard antidepressant medications and unilateral rTMS.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…[ 5 , 6 ] A recent study found that treatment regimens combining high pulse doses and multiple daily treatments of rTMS showed improved efficacy for MDD. [ 7 ] rTMS has also been proved to be an effective and safe a treatment for elderly patients with MDD. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…There is also building evidence for efficacy in PTSD and some chronic pain conditions [10,11]. "Accelerated TMS" is a potential major advancement in the field [12]. The standard protocol of TMS for depression involves one daily session distributed over six weeks [13,14], while accelerated protocols use multiple treatments per day in an attempt to accelerate response.…”
Section: Introductionmentioning
confidence: 99%